The Importance of Being a Compassionate Leader: The Views of Nursing and Midwifery Managers From Around the World - Papadopoulos, Irena; Lazzarino, Runa; Koulouglioti, Christina; Aagard, Magdeline; Akman, Ozlem; Alpers, Lise-Merete; Zorba, Akile (Sage Publications Inc, 2021)
Introduction: Despite the importance of compassionate leadership in health care, many of the existing publications do not account for the effect of culture. The aim of this study is to explore the views of nursing and midwifery managers from different countries in relation to the definition, advantages, and importance of compassion. Methodology: A cross-sectional, descriptive, exploratory online survey was conducted across 17 countries, containing both closed and open-ended questions. Data from N = 1,217 respondents were analyzed using a directed hybrid approach focusing only on qualitative questions related to compassion-giving. Results: Four overarching themes capture the study's results: (1) definition of compassion, (2) advantages and importance of compassion for managers, (3) advantages and importance of compassion for staff and the workplace, and (4) culturally competent and compassionate leadership. Discussion: Innovative research agendas should pursue further local qualitative empirical research to inform models of culturally competent and compassionate leadership helping mangers navigate multiple pressures and be able to transculturally resonate with their staff and patients.
Keywords: leadership; culture; compassion; nursing; midwifery; managers; cultural competence